2008
DOI: 10.4161/cbt.7.10.6637
|View full text |Cite
|
Sign up to set email alerts
|

Identification of side population cells from bladder cancer cells by DyeCycle Violet staining

Abstract: Side population (SP) cells can be used to identify putative cancer stem cells (CSC), but this technique is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 27 publications
4
45
0
1
Order By: Relevance
“…Such a T-IC population exists at the top of a hierarchical relationship and is capable of reconstituting all downstream populations. These results add complexity to our originally proposed T-IC model (19) and suggest BC conforms to the cancer stem cell model (19,(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 59%
“…Such a T-IC population exists at the top of a hierarchical relationship and is capable of reconstituting all downstream populations. These results add complexity to our originally proposed T-IC model (19) and suggest BC conforms to the cancer stem cell model (19,(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 59%
“…Multiple groups have used this approach to identify and isolate urothelial CSCs. She and colleagues showed that side population cells isolated from bladder cancer cell lines have selfrenewing ability, clonogenic capacity, and can initiate tumor formation when subcutaneously injected in low numbers (1 Â 10 3 ) into immunocompromised mice (36). Furthermore, expression of the ABC transporters ABCG2 and ABCB1 (also known as MDR1) was confirmed, and side population cells express the stem cell markers POU5F1 and BMI1, implying a stem-like phenotype of side population cells (36).…”
Section: Urothelial Stem Cellsmentioning
confidence: 99%
“…She and colleagues showed that side population cells isolated from bladder cancer cell lines have selfrenewing ability, clonogenic capacity, and can initiate tumor formation when subcutaneously injected in low numbers (1 Â 10 3 ) into immunocompromised mice (36). Furthermore, expression of the ABC transporters ABCG2 and ABCB1 (also known as MDR1) was confirmed, and side population cells express the stem cell markers POU5F1 and BMI1, implying a stem-like phenotype of side population cells (36). In an independent study, side population cells isolated from the T24 bladder cancer cell line showed a more quiescent cell state, asymmetric cell division, rapid cell growth, and colony formation and chemo-and radioresistance, providing further evidence for CSC enrichment (37).…”
Section: Urothelial Stem Cellsmentioning
confidence: 99%
“…There was no correlation between the proportion of SP-cells and the transformation status of the respective cell line. Strikingly, Dye cycle Violet purified non-SP cells could, upon further sub-culturing, generate a small proportion of SP cells and the authors exclude the possibility of contamination [24]. Moreover, in the bladder carcinoma cell line J82, cell cultures founded by purified SP cells displayed a sharp drop in the SP fraction immediately after seeding (i.e.…”
mentioning
confidence: 98%
“…Both Hoechst 33342 and Dye Cycle Violet have been used and both staining procedures were able to enrich for clonogenic and tumorigenic cells [22][23][24]. Surprisingly, a side-by-side comparison of both stains revealed that in some urothelial cancer cell lines, the proportion of SP cells detected by the Dye Cycle Violet staining could be far higher (up to 20 times) than for the Hoechst 33342 (e.g.…”
mentioning
confidence: 99%